Improvement of Mesenchymal Stromal Cell Proliferation and Differentiation via Decellularized Extracellular Matrix on Substrates With a Range of Surface Chemistries - Yang, Michael C.; O'Connor, Andrea J.; Kalionis, Bill; Heath, Daniel E. (Frontiers in Medical Technology, 2022)
Decellularized extracellular matrix (dECM) deposited by mesenchymal stromal cells (MSCs) has emerged as a promising substrate for improved expansion of MSCs. To date, essentially all studies that have produced dECM for MSC expansion have done so on tissue culture plastic or glass. However, substrate surface chemistry has a profound impact on the adsorption of proteins that mediate cell-material interactions, and different surface chemistries can cause changes in cell behavior, ECM deposition, and the in vivo response to a material. This study tested the hypothesis that substrate surface chemistry impacts the deposition of ECM and its subsequent bioactivity. This hypothesis was tested by producing glass surfaces with various surface chemistries (amine, carboxylic acid, propyl, and octyl groups) using silane chemistry. ECM was deposited by an immortalized MSC line, decellularized, and characterized through SDS-PAGE and immunofluorescence microscopy. No significant difference was observed in dECM composition or microarchitecture on the different surfaces. The decellularized surfaces were seeded with primary MSCs and their proliferation and differentiation were assessed. The presence of dECM improved the proliferation of primary MSCs by ~100% in comparison to surface chemistry controls. Additionally, the adipogenesis increased by 50–90% on all dECM surfaces in comparison to surface chemistry controls, and the osteogenesis increased by ~50% on the octyl-modified surfaces when dECM was present. However, no statistically significant differences were observed within the set of dECM surfaces or control surfaces. These results support the null hypothesis, meaning surface chemistry (over the range tested in this work) is not a key regulator of the composition or bioactivity of MSC-derived dECM. These results are significant because they provide an important insight into regenerative engineering technologies. Specifically, the utilization of dECM in stem cell manufacturing and tissue engineering applications would require the dECM to be produced on a wide variety of substrates. This work indicates that it can be produced on materials with a range of surface chemistries without undesired changes in the bioactivity of the dECM.